RISCO DE CONTAMINAÇÃO DE SOLOS E ÁGUAS SUBTERRÂNEAS NO ESTADO DO MARANHÃO POR ORGANOCLORADOS: SUSCETIBILIDADE DE ÁREAS DE PRESERVAÇÃO - CARREIRO, Lorena Mendes (2016)
Test of risk of contamination of soil and groundwater in Maranhão by organochlorines. Analysis of the susceptibility of ecological interest areas of the state.